Pengaruh Struktur Modal, Likuiditas, dan Profitabilitas terhadap Kemandirian BLU di Lingkungan Direktorat Jenderal Kesehatan Lanjutan - Hesti Kurniasih; Atik Djayanti (Jurnal Riset Perbankan Manajemen dan Akuntansi, 2026)
This article examines the effect of capital structure, liquidity, and profitability on the financial independence of Public Service Agency (BLU) Vertical Hospitals under Indonesia's Directorate General of Advanced Health Services, Ministry of Health. Financial independence is measured through the ratio of operating revenue to operating expenses (POBO Ratio); capital structure is proxied by the Debt to Equity Ratio (DER); liquidity by the Current Ratio (CR); and profitability by Return on Equity (ROE), substituting for Return on Assets, which is unavailable in the dataset used. The sample covers 32 BLU Vertical Hospitals over 2020-2024, selected through a census technique, yielding 160 balanced panel observations. Data were analyzed using panel regression selected through the Chow and Hausman tests, which identified the Fixed Effect Model as the best estimator. Because the classical assumption tests detected heteroscedasticity, final inference relies on White cross-section robust standard errors. Results show capital structure has an insignificant negative effect, liquidity has an insignificant positive effect, while profitability has a positive effect with weak significance (significant at 10% but not 5%). Jointly, the three variables significantly affect BLU independence, with the model explaining 69.8% of its variation, although most of this stems from heterogeneity across hospitals rather than from the three ratios themselves. These findings indicate that hospital-specific characteristics play a more dominant role in determining independence than the financial ratios alone, opening avenues for future research on contextual variables such as capital expenditure as a moderator.